Differential effects of concentric and eccentric contractions on the primary motor cortex in healthy young and elderly participants - Desachy, Marion; Héraud, Nelly; Lagarde, Julien; Pla, Simon; Varray, Alain (Frontiers in Aging Neuroscience, 2025)
IntroductionAging is associated with a decline in musculoskeletal function, particularly muscle weakness, which affects a significant proportion of older adults and is associated with reduced quality of life and increased mortality. Two major contributors to age-related muscle weakness are muscle atrophy and cortical alterations. Eccentric exercise has been identified as a promising intervention to counteract these declines, as it has the potential to increase both muscle mass and cortical activity in young people. However, while the benefits of eccentric contractions on muscle mass in older adults are well documented, their effects on cortical activity, particularly in the lower limbs, remain unclear. The aim of this study was to compare cortical activity during concentric and eccentric quadriceps contractions of young and older adults.MethodsThis prospective study included 32 healthy participants: 17 young (23 ± 4 years, 6 women, 11 mens) and 15 older (62 ± 7 years, 7 women, 8 mens). Muscle strength was assessed using an isokinetic ergometer, muscular activity with electromyography electrodes positioned on quadriceps, and cortical activity using electroencephalography (EEG). Participants performed 40 concentric and 40 eccentric voluntary contractions against 20% of their maximal voluntary isometric contraction. EEG data were processed to analyze motor-related cortical potentials, specifically the negative potential (NP). The NP was divided into two main components: latency and amplitude as indicators of cortical activity during movement preparation and execution.ResultsThere were no significant differences in participants characteristics between groups, except for age. Muscular activity was lower during eccentric than concentric contractions (p < 0.05). Cortical activity was significantly lower in older compared to young adults, which was reflected in reduced NP latency across several electrodes (Cz, p = 0.03; C4, p = 0.02; FC2, p = 0.02). However, regarding NP amplitude, it was significantly higher during eccentric contractions in Cz, C4, FC5, and C2 electrodes (p < 0.05) across both age groups.ConclusionThis study is the first to investigate cortical activity during eccentric lower limb contractions in older adults. The results suggest that eccentric contractions induce greater cortical activation compared to concentric, even in older adults who generally exhibit reduced cortical activity. These findings support the potential of eccentric as an effective intervention to improve motor function and muscle strength in older adults.